2018
DOI: 10.3389/fphys.2018.01627
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Delayed Neuromuscular Alterations Induced by Downhill Running in Trained Trail Runners: Beneficial Effects of High-Pressure Compression Garments

Abstract: Introduction: The aim of this study was to examine, from a crossover experimental design, whether wearing high-pressure compression garments (CGs) during downhill treadmill running affects soft-tissue vibrations, acute and delayed responses in running economy (RE), neuromuscular function, countermovement jump, and perceived muscle soreness.Methods: Thirteen male trail runners habituated to regular eccentric training performed two separate 40-min downhill running (DHR, –8.5°) sessions while wearing either CGs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 72 publications
(134 reference statements)
3
65
1
Order By: Relevance
“…We observed higher value of soft tissue peak acceleration for downhill speed and lower value for uphill speed compared to flat running condition. 'Muscle tuning' can be accentuated or masked especially on downhill or uphill condition (Ehrstr€ om et al 2018). As previously observed, in our study the wore of CG improve the protective effect of 'muscle tuning' by limiting STV (Ehrstr€ om et al 2018).…”
Section: Resultssupporting
confidence: 83%
“…We observed higher value of soft tissue peak acceleration for downhill speed and lower value for uphill speed compared to flat running condition. 'Muscle tuning' can be accentuated or masked especially on downhill or uphill condition (Ehrstr€ om et al 2018). As previously observed, in our study the wore of CG improve the protective effect of 'muscle tuning' by limiting STV (Ehrstr€ om et al 2018).…”
Section: Resultssupporting
confidence: 83%
“…For example, Garnier et al [58] reported greater decrements in isokinetic (concentric and eccentric) MVC torque of KE, accompanied by a greater occurrence of the peripheral component of neuromuscular fatigue, in-situ perceived exertion (in gluteus muscles) and delayed muscle pain (in KE, PF and gluteus) following a 45-min DR bout, compared to uphill and level running bouts performed at the same relative intensity (same reserve heart rate, HR). Immediately after DR, large reductions in isometric MVC force/torque of KE and PF muscles are generally reported, and may vary from − 14 to − 55% for KE [5,9,10,15,38,43, and from − 15 to − 25% for PF [9,15,43]. Similarly, a decline in muscle performance (expressed as MVC force/torque loss or endurance capacity) was reported during isokinetic muscle actions (tested from 0.52 to 5.2 rad s −1 and from 0.52 to 2.6 rad s −1 for concentric and eccentric modalities, respectively) [58,88,89], dynamic strength measurement such as counter movement jump [15,90] and muscle endurance test [91].…”
Section: Functional Muscular Alterations Following Downhill Runningmentioning
confidence: 99%
“…1). The reduction in isometric MVC force/torque generally peaks immediately post-DR [5,9,10,15,38,43,, whereas increases in blood CK [14,16,38,[40][41][42] Endurance training seems to limit the occurrence of muscle damage following DR [3,15]. Physical training has been shown to promote higher physiological muscle resistance to exercise due to a combination of neural (motor unit recruitment), morphological (muscle-tendon unit stiffness) and structural adaptations (muscle fascicle pennation angle, and fascicle length) [189,190].…”
Section: Influence Of Training Level and Downhill Running Characterismentioning
confidence: 99%
See 2 more Smart Citations